2016
DOI: 10.4238/gmr.15027936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the balance between type 1 and type 2 T helper cells on ovarian cancer

Abstract: ABSTRACT. The balance between type 1 and type 2 T helper cells (the Th1-Th2 balance) is closely correlated with cancer, but the correlation in ovarian cancer remains unconfirmed. We investigated the Th1-Th2 balance for the diagnosis, treatment, and prognostic evaluation of ovarian cancer. Fifty healthy subjects and 50 ovarian cancer patients were recruited. The levels of various cytokines were determined in sera and ovarian cancer tissues using a Th1-Th2 human cytokine array. The usefulness of TNFa, IFNg, TNFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…[ 48 ] It is suggested that Th1 adaptive immunity is essential for cancer inhibition and better outcomes. [ 49 , 50 , 51 ] These may be because of the small sample size of this study. In our further studies, we will enlarge our sample size and investigate the function of Th1 cells and IFN-γ.…”
Section: Discussionmentioning
confidence: 94%
“…[ 48 ] It is suggested that Th1 adaptive immunity is essential for cancer inhibition and better outcomes. [ 49 , 50 , 51 ] These may be because of the small sample size of this study. In our further studies, we will enlarge our sample size and investigate the function of Th1 cells and IFN-γ.…”
Section: Discussionmentioning
confidence: 94%
“…13 Such juxtaposing contributions suggest that there is a critical balance between anti-tumor and pro-tumor environments, which may often be tilted in favor of tumor growth and escape from immunological surveillance. 14,15 Previous studies have identified specific immune mediators and pathways in patient sera, ovarian carcinoma ascites and tumor lesions that may hold predictive or prognostic value. 14,[16][17][18][19][20] We hypothesized that a broader evaluation of secreted immune, inflammatory and angiogenic mediator signatures, reflecting the tumor-associated immunological environment, may associate with differential clinical prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Previous studies have identified specific immune mediators and pathways in patient sera, ovarian carcinoma ascites and tumor lesions that may hold predictive or prognostic value. 14,[16][17][18][19][20] We hypothesized that a broader evaluation of secreted immune, inflammatory and angiogenic mediator signatures, reflecting the tumor-associated immunological environment, may associate with differential clinical prognoses. In this study, we selected 44 immune, inflammatory and angiogenic mediators known to be involved in immune response to pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines can be expressed in small amounts in the normal ovaries as well [8]. Previous assessments of protein concentration of cytokines in serum and ascites of EOC patients and in supernatants of EOC cell lines have shown that there is a shift towards immunoinhibitory cytokines [8][9][10][11][12][13]. Additionally, in earlier reports from the nineties, attempts were made to assess mRNA expression for a limited number of individual cytokines in tumor tissue using Northern blot or semi-quantitative RT-PCR [14][15][16][17].…”
Section: Total Rna Extraction and Real-time Quantitative Reverse Tranmentioning
confidence: 99%